STRATEGIES USED BY ENGLISH TEACHERS IN TEACHING ENGLISH AS A FOREIGN LANGUAGE AT SMK NEGERI 2 PULAU-PULAU BATU SOUTH NIAS - Sohan Putra Amajihono; Arsen Pasaribu; Huertas Abrila (Merwin Publisher, 2025)
This study aimed to find and explain English teachers’ strategies used in teaching English as a foreign language. The types of this study is descriptive qualitative research. The subjects of this study were students of SMK Negeri 2 Pulau-Pulau Batu majoring in ULP (Usaha Perjalanan Wisata) which consists of 37 students and two English teachers who taught in different classes with the same major. Moreover, the researcher collect the data by using the instruments of the study. Instrument used is survey questionnaires consisting of open-ended and close-ended questionnaires. In addition, the researcher interviews both teachers and students also. The result of this study showed that the teachers used some strategies in teaching English as a foreign language. Teaching strategies used by the teachers such as discussion, small-group work, co-operative learning, and role play. Besides of that, teachers used other strategy to accommodate students’ interest in learning English as foreign language such as using PPT, films, music, cards, poster and other interesting media.